Water implications of large-scale land acquisitions in Ghana - Williams, Timothy O.; Gyampoh, B.; Kizito, Fred; Namara, Regassa E. (2012)
This paper examines the water dimensions of recent large-scale land acquisitions for biofuel production in the Ashanti, Brong-Ahafo and Northern regions of Ghana. Using secondary sources of data complemented by individual and group interviews, the paper reveals an almost universal lack of consideration of the implications of large-scale land deals for crop water requirements, the ecological functions of freshwater ecosystems and water rights of local smallholder farmers and other users. It documents the factors responsible for this apparent oversight including the multiplicity of land and water governance systems, sharp sectoral boundaries between land and water policies, property rights and institutions, outdated statutes, poorly resourced and ineffective regulatory agencies, and unequal power relations in land acquisition deals. The paper shows that due to a lack of an approach that jointly considers land and water management policies and institutions in acceding to large-scale land deals, the benefits derived by local people were insufficient to cover the involuntary permanent loss of their water rights and livelihoods and the risks posed to ecosystem services. Options for establishing alternative institutional arrangements that will allow water availability, use and management as well as social and environmental standards to be factored, ex ante, into large-scale land deals are explored.